Analisis Faktor yang Mempengaruhi Tingkat Pengangguran di Provinsi Jawa Timur Tahun 2006-2014 - Laurensius Surya A. U.; Nanik Istiyani; Rafael Purtomo (UPT Penerbitan Universitas Jember, 2018)
Unemployment is a major problem in macroeconomics. The study aims to determine the effect Rate of Gross Regional Domestic Product (GDP), Population, and the regional minimum wage (UMR) of the Unemployment Rate in East Java. Analysis method used in this research is panel data regression with fixed effect model approach (FEM). This study uses secondary data from the Central Bureau of Statistics (BPS). The data used in this research are open unemployment rate, GDP rate, population, regional minimum wage in Provinsi of East Java in 2006-2014. Based on the analysis, it can be seen that the variable rate of the GDP, and the local minimum wage and a significant negative effect on the variable Unemployment Rate in East Java province. Variable population no significant and negative effect on the variable unemployment rate in East Java Province.The results of this study indicate that the variable rate of Gross Regional Domestic Product (GDP) has a significant influence based on it is expected that the government can support investment in the small and medium enterprise sector.Keywords: Unemployment Rate, Rate of Gross Regional Domestic Product (GDP), Population, Regional Minimum Wage (UMR)